Social Networks and Legal Transfers: A Study on the Contractual Relations of Afghan Taxi Drivers - Choudhury , Nafay (University of Darussalam Gontor Press, 2025)
This study examines the phenomenon of legal transfers in developing countries through the lens of social network analysis, using the case of Afghan taxi drivers to explore the interaction between formal legal reforms and embedded social norms. Drawing on field research conducted in Kabul, the paper investigates how taxi drivers conduct their contractual affairs in the context of a weak formal legal system. Despite significant international efforts to transplant formal contract law regimes and strengthen judicial institutions in Afghanistan, the findings reveal that formal law plays a minimal role in regulating everyday transactions. Instead, drivers rely heavily on social networks—particularly guarantors—whose legitimacy stems not from state authority, but from trust and reputation within the community. Intriguingly, these guarantors increasingly include government-affiliated individuals, whose bureaucratic registration makes them traceable and thus pragmatically valuable, while still operating within informal norms. The paper argues that rather than replacing traditional norms, legal reforms have been absorbed into existing social networks, resulting in a hybrid regulatory model. This underscores the resilience of local social structures and challenges conventional assumptions in law and development discourse that equate legal reform with normative transformation. By introducing social network analysis into legal transfer studies, the paper provides a more nuanced framework to understand how legal ideas are localized, reinterpreted, or resisted. The study ultimately advocates for greater contextual sensitivity in assessing the impact of legal transfers, recognizing that recipient environments are governed not merely by legal institutions but by complex webs of interpersonal relationships and social meaning.